Implementasi Pembelajaran Kitab Alala dalam Pembentukan Karakter Siswa Kelas VII di Madrasah Tsanawiyah Al-Azhar Peterongan Jombang - Amelia Dwi Lestari; Aina’ul Mardliyah; Siti Asiah (YASIN, 2026)
Although the teaching of classical Islamic texts has been widely studied in the context of Islamic education, research specifically examining the implementation of Kitab Alala instruction in shaping students’ character in madrasahs remains limited. This study aimed to describe the implementation of Kitab Alala instruction, analyze its contribution to students’ character development, and identify the supporting and inhibiting factors affecting its implementation at MTs Al-Azhar Peterongan Jombang. The study employed a qualitative approach with a field research design. The research informants consisted of the head of the madrasah, the Kitab Alala teacher, the Grade VII homeroom teacher, and Grade VII students selected purposively. Data were collected through interviews, observations, and documentation and were subsequently analyzed using the Miles and Huberman interactive model, which includes data condensation, data display, and conclusion drawing. The results showed that Kitab Alala instruction was implemented through the stages of planning, implementation, and evaluation using the mubasyarah method. The instruction contributed to the development of students’ discipline, responsibility, and courtesy. Its successful implementation was supported by teacher competence, the religious environment of the madrasah, and positive habituation, whereas the inhibiting factors included limited learning facilities, variations in students’ ability to understand the material, and limited proficiency in Arabic and the Pegon script. This study concludes that Kitab Alala instruction can serve as an effective strategy for instilling character values when supported by systematic planning, exemplary teacher conduct, and a conducive educational environment. These findings enrich the literature on character education based on classical Islamic texts and provide practical implications for madrasahs in improving instructional quality and strengthening students’ character development. Keywords: Kitab Alala; Madrasah Tsanawiyah; Classical Islamic Text Instruction; Character Development; Islamic Education